OPTIMALISASI PENGUASAAN TEHNOLOGI INDUSTRI PERTAHANAN MELALUI PEMBELIAN KOMPONEN PEMELIHARAAN ALPALHANKAM - Chardes Marihot Tampubolon; Sovian Aritonang (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
Currently, all countries in the world are competing in mastering technology, especially defense technology. Such as America and European countries that compete in the development of defense technology. Various strategies are carried out by all countries in the world to master technology. One strategy that is widely used by every country in the world in mastering technology is the Offset mechanism when purchasing Alpalhankam, including Indonesia. Currently, in mastering technology, Indonesia has implemented a defense offset mechanism through the purchase of defense equipment (Tier 1) such as submarines and fighter aircraft. Indeed, in the purchase of defense equipment, the transfer of mastery of technology includes the main components (Tier 2) and supporting components (Tier 3). However, many of these components are purchased from abroad outside of the purchase of Alutsista for the maintenance of the Alutsista that we already have but have not implemented the Offset strategy, this paper discusses the efficiency of the offset mechanism for purchasing components (Tier 2 and Tier 3) which are carried out outside the purchase of Alutsista (Tier 1 ) by sharpening and optimizing the existing regulations, the discussion is carried out through a review of the Literature Review